ULAMA AND UMARA: ACTORS WHO FORMED ISLAMIC CIVILIZATION IN THE SULTANATE OF BIMA (International Conference on Social and Islamic Studies, 2021)
This paper aims to explain the role of Ulama and Umara as important actors in the formation of Islamic civilization in the Sultanate of Bima. The method used in tracking the supporting data is the historical writing method which consists of heuristics, sourcecriticism, interpretation and historiography. The historical method is useful in reconstructing the past systematically in order to reach a complete conclusion. Theresults of the study show that the relationship between Ulama and Umara can be tracedsince the wave of Islamization in the Bima Sultanate. Ulama with religious authorit yconfirmed Islam (as a new civilization) in a political institution (sultanate) controlled byUmara. While Umara in the context of the Sultanate of Bima is a Sultan as a figure holding the reins of power. Ulama with religious authority are eager to develop da'wah and fully support the Sultan's efforts in confirming Islam as the official religion in his territory. Thus, the role and position of the Ulama and Umara became very important actors for the formation of a new civilization with an Islamic spirit in the Sultanate ofBima.